PHB/CHIT Scaffold as a Promising Biopolymer in the Treatment of Osteochondral Defects-An Experimental Animal Study - Petrovova, Eva; Tomco, Marek; Holovska, Katarina; Danko, Jan; Kresakova, Lenka; Vdoviakova, Katarina; Simaiova, Veronika; Kolvek, Filip; Hornakova, Petra; Toth, Teodor; Zivcak, Jozef; Gal, Peter; et al. (Polymers, 2021)
Biopolymer composites allow the creation of an optimal environment for the regeneration of chondral and osteochondral defects of articular cartilage, where natural regeneration potential is limited. In this experimental study, we used the sheep animal model for the creation of knee cartilage defects. In the medial part of the trochlea and on the medial condyle of the femur, we created artificial defects (6 × 3 mm2) with microfractures. In four experimental sheep, both defects were subsequently filled with the porous acellular polyhydroxybutyrate/chitosan (PHB/CHIT)-based implant. Two sheep had untreated defects. We evaluated the quality of the newly formed tissue in the femoral trochlea defect site using imaging (X-ray, Computer Tomography (CT), Magnetic Resonance Imaging (MRI)), macroscopic, and histological methods. Macroscopically, the surface of the treated regenerate corresponded to the niveau of the surrounding cartilage. X-ray examination 6 months after the implantation confirmed the restoration of the contour in the subchondral calcified layer and the advanced rate of bone tissue integration. The CT scan revealed a low regenerative potential in the bone zone of the defect compared to the cartilage zone. The percentage change in cartilage density at the defect site was not significantly different to the reference area (0.06-6.4%). MRI examination revealed that the healing osteochondral defect was comparable to the intact cartilage signal on the surface of the defect. Hyaline-like cartilage was observed in most of the treated animals, except for one, where the defect was repaired with fibrocartilage. Thus, the acellular, chitosan-based biomaterial is a promising biopolymer composite for the treatment of chondral and osteochondral defects of traumatic character. It has potential for further clinical testing in the orthopedic field, primarily with the combination of supporting factors.
Keywords: sheep model; cartilage; regeneration; chitosan; biopolymer